2019
DOI: 10.1002/ejic.201801492
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Lanthanide Complexes Based on Tetraazacyclolamidophenol Ligand with Field‐Induced Slow Magnetic Relaxation, Luminescent and SHG Properties

Abstract: Two multifunctional lanthanide complexes, namely [Dy(HL)]·CH3OH (1) and [Er(HL)]·CH3OH (2), [H4L = N,N′,N′′,N′′′‐tetra(3,5‐dimethyl‐2‐Hydroxybenzyl)‐1,4,7,10‐tetraazacyclododecane] were synthesized and structurally characterized. Complexes 1 and 2 are isomorphic and crystallize in the non‐centrosymmetric orthorhombic space group Pca21. Their structure consists of one seven‐coordinated LnIII ion with the coordination geometry of trigonal prism, one HL3– ligand and one lattice methanol molecule. They exhibit sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…[77] This complex has the Dy III centre in an early ideal PB geometry with three anionic chloride donors in equatorial positions, and showed weak SMM behaviour,w ith a U eff of 36 K. [77] Using the large multi-dentate N 4 TzcAl igand (Figure 8), Wen et al reported am ultifunctional SMM (7.19 [78] )r ecently,w hich contains a Dy III centre with four N-donors and three O-donors showing field-induced SMM behaviour as wella ss trong fluorescent emission. [78] Complexes 7.20 and 7.21 are rare examples of chiral mononuclear seven-coordinateS MMs containing large macrocyclic ligands( Figure 8). [79] The Dy III centres in these homochiral complexes sit in as addle-type conformation; 7.21 showsw eak field-induced SMM behaviour.…”
Section: Cn 7c Omplexesmentioning
confidence: 99%
See 2 more Smart Citations
“…[77] This complex has the Dy III centre in an early ideal PB geometry with three anionic chloride donors in equatorial positions, and showed weak SMM behaviour,w ith a U eff of 36 K. [77] Using the large multi-dentate N 4 TzcAl igand (Figure 8), Wen et al reported am ultifunctional SMM (7.19 [78] )r ecently,w hich contains a Dy III centre with four N-donors and three O-donors showing field-induced SMM behaviour as wella ss trong fluorescent emission. [78] Complexes 7.20 and 7.21 are rare examples of chiral mononuclear seven-coordinateS MMs containing large macrocyclic ligands( Figure 8). [79] The Dy III centres in these homochiral complexes sit in as addle-type conformation; 7.21 showsw eak field-induced SMM behaviour.…”
Section: Cn 7c Omplexesmentioning
confidence: 99%
“…[116,117,121] Among higher-coordinate (CN > 5) mononuclear Er III alkoxide and aryloxide SMMs,n one show improved SMM behaviour over the Er III COT family or Dy III derivatives of highercoordinate alkoxide and aryloxide SMMs. [78,79,81,85,89,[122][123][124][125]…”
Section: Enhancing Molecularrigidity By Ligand Functionalisationmentioning
confidence: 99%
See 1 more Smart Citation
“…They are the most sought after metal ions in the pursuit of single-molecule magnets (SMM) due to their high spin values and magnetic anisotropy, while the wide range of intense, narrow, and long-lived emission bands of their complexes more than qualify them as new-age luminescent materials. More recently, the combination of these two properties to produce multifunctional opto-magnetic Ln­(III) complexes is the new craze for research in this area. For design of photoluminescent SMM complexes, the choice of the metal ion is the most crucial in terms of the kind of anisotropy in its electron density (prolate or oblate) followed by its emitting state and sensitizing mechanism. The latter depends wholly on the choice of ligand that could both sensitize the ion as well as produce a ligand field further augmenting the anisotropy of the metal ion.…”
Section: Introductionmentioning
confidence: 99%
“…Following these perspectives, we and other groups focused on the challenge to break the symmetry of the crystalline phases based on emissive Ln-SMMs to induce SHG activity. 276,307,308 While the other groups focused on enantiomeric organic ligands that ensure all of the necessary features, SHG-activity, luminescence, and magnetic anisotropy, we took advantage of the heterometallic approach that utilizes octacyanidometallate ions of Mo(IV) and W(IV) (Fig. 18).…”
Section: Second-harmonic Generation Activity Of Acentric Luminescent ...mentioning
confidence: 99%